Kaji Eksperimental Variasi Temperatur Dan Putaran Pada Pengelasan Friction Stir Welding Menggunakan Material Polypropilene (PP) - Mhd Irvan Irwana; Dodi Sofyan Arief; M. Dalil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Welding according to DIN (Deutsche Industrie Norman) is a metallurgical bonding on the connection is done in the melting or liquid state. In other words, the welding is the joining of two pieces of metal into one doneby way of heating or melting, where both ends of the object that will be spliced with eyes melt made the pin on the tool or the heat gained from the pins on the rounds a specified rpm. each specimen, material AISI 4140 steel is used with a diameter of 6 mm pin welding position horizontally (flat), the used temperature 70 ° c, 75 ° c, 80 °c, and a round of rpm used 400 rpm, 500 rpm, 700 rpm, in the execution of welding the welding method using FSW (Friction Stir Welding). Then pull the values taken on the area of welding. From the results of the research of pull, the value of the temperature of 75 ° c with round 700 rpm higher tensile strength of temperature of 70 ° cand 80 ° c.Keyword : Temperature, Rpm Spin, Friction Stir Welding, Welding, Surface Polypropilene.